India working - Harriss-White , Barbara (Cambridge, 2003)
By drawing on her extensive fieldwork in India, and on the adjacent theoretical and empirical literature, Barbara Harriss-White describes the working of the Indian economy through its most important social structures of accumulation: labour, capital, the State, gender, religious plurality, caste and the economic organisation of physical space. The author's intimate knowledge of the country enables her to convey vividly how India's economy is being socially regulated. Her conclusion challenges the prevailing notion that liberalisation releases the economy from political interference, and leads to a postscript on the economic base for fascism in India. This is a sophisticated and compelling book, by a distinguished scholar, for students of economics, as well as for those studying the region.
Keywords: India-Economic conditions-1947